me ajudem nessas duas questões por favor!!
Anexos:
![](https://pt-static.z-dn.net/files/d03/3cf00b668d1813e4fd05958fc4aa8f2f.jpg)
Soluções para a tarefa
Respondido por
1
2°)
(x + 1)² = x² + 2x + 1
( x- 1 )² = x²- 2x +1
x² +2x +1 - x²-2x + 1 = 2
3°)
A = l²
A = (6x-2)² = 36x² - 24x + 4
(x + 1)² = x² + 2x + 1
( x- 1 )² = x²- 2x +1
x² +2x +1 - x²-2x + 1 = 2
3°)
A = l²
A = (6x-2)² = 36x² - 24x + 4
Perguntas interessantes
Música,
10 meses atrás
História,
10 meses atrás
Matemática,
10 meses atrás
História,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás